2016
DOI: 10.1080/17435390.2016.1181808
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ortho ester) nanoparticles targeted for chronic intraocular diseases: ocular safety and localization after intravitreal injection

Abstract: Treatment of posterior eye diseases is more challenging than the anterior segment ailments due to a series of anatomical barriers and physiological constraints confronted by drug delivery to the back of the eye. In recent years, concerted efforts in drug delivery have been made to prolong the residence time of drugs injected in the vitreous humor of the eye. Our previous studies demonstrated that poly(ortho ester) (POE) nanoparticles were biodegradable/biocompatible and were capable of long-term sustained rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Posterior segment eye diseases -such as diabetic retinopathy and age-related macular degeneration -are vision threatening, remain challenging to treat and increasingly affect a larger proportion of the populations of industrial nations due to increased life expectancy, poor lifestyle and diet (Congdon et al, 2003;Yau et al, 2015). To access the posterior segment of the eye and bypass ocular physiological barriers, nanomedicines are often injected into the vitreous (Geng et al, 2014;Li et al, 2016;Peeters et al, 2005;Zhao et al, 2017;Giannaccini et al, 2014;Natarajan et al, 2014;Sakurai et al, 2001;Thakur et al, 2014). The vitreous fills the vitreous cavity of the eye and has a number of physiological roles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior segment eye diseases -such as diabetic retinopathy and age-related macular degeneration -are vision threatening, remain challenging to treat and increasingly affect a larger proportion of the populations of industrial nations due to increased life expectancy, poor lifestyle and diet (Congdon et al, 2003;Yau et al, 2015). To access the posterior segment of the eye and bypass ocular physiological barriers, nanomedicines are often injected into the vitreous (Geng et al, 2014;Li et al, 2016;Peeters et al, 2005;Zhao et al, 2017;Giannaccini et al, 2014;Natarajan et al, 2014;Sakurai et al, 2001;Thakur et al, 2014). The vitreous fills the vitreous cavity of the eye and has a number of physiological roles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“… [ 99 ] Poly(vinyl alcohol) (PVA) Increase viscosity The slow rate of degradation strong solvents utilized in the synthesis [ 165 ] Poly(glycolic acid) (PGA) Increase viscosity fast rate of degradation fragile mechanical characteristics [ 166 ] Poly(glycolic acid – co – lactic acid) (PLGA) Increase viscosity The most popular polymer is utilized in ocular medication delivery, with an adaptable rate of degradation and water solubility. Byproducts of acidic degradation [ 167 ] Poly(lactic acid) (PLA) Increase viscosity Easy to process, synthesized from natural sources The slow rate of degradation [ 168 ] Poly(orthoester) (POE) Increase viscosity surface erosion degradation not extensively researched for medication delivery applications [ 168 ] Poly(methacrylates) and derivatives (PMMA) Increase viscosity a well-known ocular polymer that is affordable Non-biodegradable [ 122 ] Poly(acrylic acid) PAA Increase viscosity mucoadhesive, highly easily soluble in water breakdown into acidic byproducts [ 126 ] Gelatin Increase viscosity Gelling, emulsifying, plus foaming appearances fairly accessible Inexpensive Not antigenic like collagen Groups may be chemically changed Not for long-tenure drug conveyance arr...…”
Section: Excipients Castoff In Ocular Inventions For Modified Drug Co...mentioning
confidence: 99%
“…The injectable drug depot is currently in clinical trials and has shown controlled release of sunitinib malate for up to 6 months post injection (32). POE-based nanoparticles maintained vitreous localization in rabbits after intravitreal injection for up to 14 days with minimal increases in IOP (150). Work by Fu et al Micelles are core/shell structures formed by amphiphilic block copolymers with hydrophobic and hydrophilic domains, and are often <100 nm in size.…”
Section: Micro-and Nano-scale Technologiesmentioning
confidence: 99%